Ancient faces (New York)
1 online resource
Keywords: From the first major discoveries a century ago, the painted portraits of Roman Egypt were a revelation to scholars and the public alike, and the recent finding of a new cache of these gilded images, which made national headlines, have only heightened their mystery and appeal. Published to coincide with a new major exhibition of these portraits, Ancient Faces is the most comprehensive, up-to-date survey of these astonishing works of art.Dating from the later period of Roman rule in Egypt, shortly before the birth of Christ, the painted mummy portraits are among the most remarkable products of the ancient world, a fusion of the traditions of pharonic Egypt and the Classical world. They are historical and cultural objects of outstanding importance and beauty, superb works of art that represent some of the earliest known examples of life-like portraiture. Though the subjects of the portraits believed in the traditional Egyptian cults, which offered them a firm prospect of life after death, they also wished to be commemorated in the Roman manner, with their fashion of dress and adornment signaling their status in life. Despite their ancient history, these portraits speak to the modern eye with a beauty and intensity that would be lost to portraiture until the Renaissance.